Tinjauan Kemampuan Tenaga Kesehatan pada Pengelolaan Sistem Informasi Kesehatan (SIK) Di Puskesmas Sulamadaha Kecamatan Pulau Ternate Tahun 2013 - Samad Hi Husen; Irma B Lewa (UPPM Poltekkes Kemenkes Ternate, 2014)
Abstract : Health information system is an information management at all levels of government systematically for service delivery to the public. Legislation that mentions the health information system is Kepmenkes No. 004/Menkes/SK/I/2003 on the policy and strategy of decentralization in health and Kepmenkes No. 932/Menkes/SK/VIII/2002 on the implementation of the instructions of health information reporting system development district / the city. It's just the two of contents Kepmenkes contains weaknesses which are both just looked at the health information system from the point of the field of health management, do not utilize state of the art technology and no information relating to the national information system. Information and communication technology are also not yet elaborated so that the data presented are not appropriate and not timely. Based on the background of the problem, it can be argued formulation of the problem